Social Movements in Latin America - Petras, J. author. aut Link
XI, 274 p.
Keywords: The authors trace out the development of capitalism and U.S. imperialism in Latin America in the latest phase of this development, from the installation of the new world order of neoliberal globalization in the early 1980s to the present when U.S. imperialism is held at bay, neoliberalism is in decline, and capitalism is in crisis.